2021
DOI: 10.4103/sjopt.sjopt_277_21
|View full text |Cite
|
Sign up to set email alerts
|

Presumed acute suppurative bacterial dacryoadenitis with concurrent severe acute respiratory syndrome coronavirus-2 infection

Abstract: Acute suppurative bacterial dacryoadenitis (ASBD) was not reported to occur following severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. We are presenting a unique case of concurrent presumed ASBD with SARS-CoV-2 infection. A 23-year-old previously healthy male presented with right upper eyelid swelling and pain over the lacrimal gland area for 3 days. Before his visit, the patient was tested positive for SARS-CoV-2 infection after experiencing mild flu-like symptoms, despite being vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Viral infection, particularly Ebstein-Barr virus, is the most common etiology in children and young adults 148 . Dacryoadenitis related to COVID-19 infection has been reported as isolated case reports 147–150 . The mean age of patients in the published literature was 22.2 years (median 23 y, 6 mo–36 y) with symptoms developing at a mean of 15.2 days (median 12 d, 7–30 d) after the diagnosis/onset of symptoms of COVID-19.…”
Section: Orbital Manifestations Of Coronavirus Disease 2019mentioning
confidence: 99%
See 1 more Smart Citation
“…Viral infection, particularly Ebstein-Barr virus, is the most common etiology in children and young adults 148 . Dacryoadenitis related to COVID-19 infection has been reported as isolated case reports 147–150 . The mean age of patients in the published literature was 22.2 years (median 23 y, 6 mo–36 y) with symptoms developing at a mean of 15.2 days (median 12 d, 7–30 d) after the diagnosis/onset of symptoms of COVID-19.…”
Section: Orbital Manifestations Of Coronavirus Disease 2019mentioning
confidence: 99%
“…The patient improved after a course of IV antibiotics and methylprednisolone. Almater et al 150 reported a case of presumed acute suppurative bacterial dacryoadenitis 10 days after the diagnosis of COVID-19.…”
Section: Orbital Manifestations Of Coronavirus Disease 2019mentioning
confidence: 99%